Functional Ionic Liquid Polymer Stabilizer for High‐Performance Perovskite Photovoltaics. Issue 16 (9th March 2023) - Shen, Yunxiu; Xu, Guiying; Li, Jiajia; Lin, Xia; Yang, Fu; Yang, Heyi; Chen, Weijie; Wu, Yeyong; Wu, Xiaoxiao; Cheng, Qinrong; Zhu, Jian; Li, Yaowen; et al.
Abstract: The stability‐related issues arising from the perovskite precursor inks, films, device structures and interdependence remain severely under‐explored to date. Herein, we designed an ionic‐liquid polymer (poly[Se‐MI][BF4 ]), containing functional moieties like carbonyl (C=O), selenium (Se + ), and tetrafluoroborate (BF4 − ) ions, to stabilize the whole device fabrication process. The C=O and Se + can coordinate with lead and iodine (I − ) ions to stabilize lead polyhalide colloids and the compositions of the perovskite precursor inks for over two months. The Se + anchored on grain boundaries and the defects passivated by BF4 − efficiently suppress the dissociation and migration of I − in perovskite films. Benefiting from the synergistic effects of poly[Se‐MI][BF4 ], high efficiencies of 25.10 % and 20.85 % were exhibited by a 0.062‐cm 2 device and 15.39‐cm 2 module, respectively. The devices retained over 90 % of their initial efficiency under operation for 2200 h. Abstract : An ionic‐liquid polymer additive (poly[Se‐MI][BF4 ]) is developed to stabilize perovskite precursor inks used to fabricate perovskite solar cells (pero‐SCs). A chemical homogeneity of the inks contributes to improving the quality of perovskite films by stabilizing the colloids and compositions for over two months. Moreover, polymers anchored at the grain boundaries can further suppress the migration of I − ions. Thus, the pero‐SCs exhibit overall improved stability and efficiency.